The MBN approach the case of Barangay Sto. Niño in Naujan, Oriental Mindoro - Cordero, Rosa R. (1999)
Naujan, a Galing Pook awardee, attributes its success in applying the Minumum Basic Needs (MBN) approach in its poverty alleviation program to the participatory and vibrant leadership style of its mayor. One of the municipality's pilot barangays in adopting the MBN approach, Barangay Sto. Niño, has likewise become a showcase barangay and has been a favorite study tour site because of its successful implementation of MBN programs. Community participation and democratic management style of the municipal mayor and barangay captain constitute the core foundations of the localities' accomplishments in addressing the issue of poverty at the municipal and barangay levels.
Keywords: Minimum Basic Needs (MBN) Approach -- Naujan (Oriental Mindoro); Basic needs -- Case studies -- Oriental Mindoro; Galing Pook Awards Program; Local development program; Social Reform Agenda (SRA)